2019
DOI: 10.1016/j.corsci.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ag participating the electrochemical migration of 96.5Sn-3Ag-0.5Cu alloy

Abstract: Ag participating the electrochemical migration (ECM) of SnAg based alloys is still controversial. In this work, Ag + concentration in electrolyte layer and Ag distribution in dendrites formed during the ECM of 96.5Sn-3Ag-0.5Cu alloy were investigated using Inductively Coupled Plasma Source Mass Spectrometer and Scanning Transmission Electron Microscopy, respectively. The results show that Ag + can be detected in electrolyte layer when the anodic polarization potential applied on the 96.5Sn-3Ag-0.5Cu alloy is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 19 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…However, dissolution of IMC can occur if the applied potential is higher than the critical potential for the dissolution of IMC. Zhong et al 122 reported that Ag dissolved and escaped from Ag 3 Sn at 2.38 V vs saturated calomel electrode (SCE), resulting in the cathodic deposition of Ag + in the ECM of SAC305 alloy.…”
Section: Flux Of Ions Ion Drift Velocity Concentration Of Ions 13mentioning
confidence: 99%
“…However, dissolution of IMC can occur if the applied potential is higher than the critical potential for the dissolution of IMC. Zhong et al 122 reported that Ag dissolved and escaped from Ag 3 Sn at 2.38 V vs saturated calomel electrode (SCE), resulting in the cathodic deposition of Ag + in the ECM of SAC305 alloy.…”
Section: Flux Of Ions Ion Drift Velocity Concentration Of Ions 13mentioning
confidence: 99%
“…It can be considered that these hydroxides/oxides are electro-reduced as the growing dendrites at the cathode. 11,40 In our Cu−Ag alloy case, the reduction of Cu(OH) 2 /CuO is more difficult than that of AgOH/Ag 2 O because of their higher redox potential, thereby slowing down the overall migration ratio. This can be verified by the morphology of the written Cu electrodes after the water-drop test (see Figure S9), where severe oxidation of electrodes can be observed instead of the dendrites within their spacing.…”
Section: ■ Results and Discussionmentioning
confidence: 98%